Evaluation of the risk assessment matrix: a mental health triage tool. Issue 1 (22nd December 2008) - Patel, A S; Harrison, A; Bruce-Jones, W
Abstract : Background: The Risk Assessment Matrix (RAM) is a mental health triage tool designed to assist emergency department (ED) staff to make rapid and accurate assessment of a patient with a suspected or actual mental health problem, and to identify patients at immediate risk of self-harm. A study was conducted to evaluate the effectiveness of this triage tool. Methods: Using a naturalistic retrospective study design, all patients attending the ED with an actual or suspected mental health problem over a 2-month period were identified to determine if any association existed with the level of risk ascertained at assessment by ED staff using the RAM and the patient's final outcome of their management. A questionnaire was administered to ED staff to determine face and content validity. Results: 202 patients were identified, 155 of whom met the inclusion criteria. Those classified medium or high risk by ED staff were significantly more likely to be referred to mental health services for further assessment, and to be admitted to an inpatient psychiatric units or have involvement of home intervention/crisis teams. Analysis showed that a significant number of respondents found the RAM useful in making triage and ongoing management decisions, indicating that the tool had strong face and content validity. Conclusion: A preliminary interpretation of the results of this study suggests the RAM is sensitive in identifying patients who warrant further urgent mental health intervention and is an effective mental health triage tool. Further prospective studies are needed to provide a more robust evidence base of the use of the RAM in the emergency setting.